Simultaneous analysis of 10 trihalomethanes at nanogram per liter levels in water using solid-phase microextraction and gas chromatography mass-spectrometry - Allard, Sebastien; Charrois, Jeffrey; Joll, Cynthia; Heitz, Anna (Elsevier BV, 2012)
Trihalomethanes are predominantly formed during disinfection of water via reactions of the oxidant with natural organic matter. Even though chlorinated and brominated trihalomethanes are the most widespread organic contaminants in drinking water, when iodide is present in raw water iodinated trihalomethanes can also be formed. The formation of iodinated trihalomethanes can lead to taste and odor problems and is a potential health concern since they have been reported to be more toxic than their brominated or chlorinated analogs. Currently, there is no published standard analytical method for I-THMs in water. The analysis of 10 trihalomethanes in water samples in a single run is challenging because the iodinated trihalomethanes are found at very low concentrations (ng/L range), while the regulated chlorinated and brominated trihalomethanes are present at much higher concentrations (above μg/L). An automated headspace solid-phase microextraction technique, with a programmed temperature vaporizer inlet coupled with gas chromatography-mass spectrometry, was developed for routine analysis of 10 trihalomethanes i.e. bromo-, chloro- and iodo-trihalomethanes in water samples. The carboxen/polydimethylsiloxane/divinylbenzene fiber was found to be the most suitable. The optimization, linearity range, accuracy and precision of the method are discussed. The limits of detection range from 1 ng/L to 20 ng/L for iodoform and chloroform, respectively. Matrix effects in treated groundwater, surfacewater, seawater, and secondary wastewater were investigated and it was shown that the method is suitable for the analysis of trace levels of iodinated trihalomethanes in a wide range of waters.The method developed in the present study has the advantage of being rapid, simple and sensitive. A survey conducted throughout various process stages in an advanced water recycling plant showed the presence of iodinated trihalomethanes at ng/L levels.